Research on Irrigation System Modeling and Group Control Strategy in Agricultural Planting Base - Jie Dong, Zhaoping Meng, Zheng Wang, Lei Zheng (Forest Chemicals Review)
In order to improve irrigation efficiency and achieve high output and benefit of crops with less irrigation water, this paper introduces the specific situation of the planting base. Then, it gives the model of the irrigation water volume and estimates the daily irrigation water consumption. In addition, according to the distributed characteristics of pump wells in the base, the group control strategy of using wireless communication network to complete the main control room and 9 distributed pump wells is designed. Practice has proved that the effect of water-saving irrigation is obvious.